Study Forest Degradation in Kalimantan using NDVI SPOT Vegetation - Widjojo, Suharto; Darmawan, Mulyanto (Badan Informasi Geospasial in Partnership with MAPIN, 2011)
AbstractKalimantan tropical rain forest (KTRF), for many years, has been subject for timber extraction, agriculture and plantation expansion, as well as settlement. Although it has experiencing ever land clearing, forest degradation both in spatial and temporal are poorly studied. In this study SPOT Vegetation were applied to scale up the understanding of forest degradation in KTRF. In the initial stage, NDVI SPOT Vegetation 10 dayâs composite was evaluated for phenological analysis. Secondly, K-mean classification and Knowledge Base Expert System (KBSE) method were applied to nine phenological metrics (Onset, End, Max, Min, AMP, RtUp, RtDn, and DUR, TIN) to calculate proportion of forest (Pof) and connectivity of forest with other non forest (Cof). Finally, the Geometrical shapes of forest were evaluated to understand forest degradation in Kalimantan forest. Result found that about 46% of Kalimantan forest has been threatened or experience with forest clearance which correspond to plantation and agriculture crops. 54% of natural forest was corresponding to transitional forest, perforated and edge forest at about 8%, 9% and 37% respectively.Keywords: Kalimantan, Rain Forest, DegradationÂ AbstrakHutan Hujan BasahKalimantan, dalam beberapa tahun, berperan sebagai pemasok kayu gelondongan, pengembangan wilayah pertanian dan perkebunan, demikian pula sebagai pemukiman. Walaupun telah banyak lahan yang di rambah, sangat sedikit studi kerusakan hutan secara spasial dan temporal.Dalam studi ini digunakan SPOT Vegetasi untuk mengetahui skala kerusakan hutan di Hutan Hujan BasahKalimantan. Dalam langkah awal, gabungan 10 hari Citra NDVI SPOT Vegetasi dievaluasi untuk analisa Fenologi, Kemudian digunakan metode klasifikasi K-mean dan Knowledge Base Expert System (KBSE) terhadap Sembilan parameter Fenologi (Onset, End, Max, <in, AMP, RtUp, RtDn, dan DUR, TIN) untuk menghitung proporsi hutan (Pof),dan hubungan antara hutan dengan non hutan (Cof). Akhirnya, bentuk Geometris dari pada hutan dievaluasi untuk mengetahui kerusakan hutan di Kalimantan. Hasilnya dijumpai bahwa sekitar 46% hutan Kalimantan telah di babat dengan cara pembukaan hutan untuk perkebunan dan lahan pertanian. 54% dari hutan alam, berupa hutan transisi 8%, hutan perforasiÂ 9%, dan hutanpinggiran 37%.Kata kunci: Kalimantan, Hutan Hujan Basah, Degradasi,